2013
DOI: 10.2478/johr-2013-0018
|View full text |Cite
|
Sign up to set email alerts
|

Propagation in vitro of alstroemeria ligtu hybrid through direct organogenesis from leaf base

Abstract: In the present study, multiplication efficiency of Alstroemeria ligtu hybrid was investigated. Bases of the first seedling leaves grown in vitro were used as initial explants. The explants were cultured in the MS media containing 3% sucrose, 0.7% agar at pH 5.8, five N6-benzylaminopurine (BAP) concentrations (0, 0.5, 1, 1.5 and 2 mg·1-1) and three indole-3-butyric acid (IBA) concentrations (0, 0.1 and 0.2 mg·1-1). The cultures were incubated at 21 ± 2 °C under photoperiod 16/8. After three subculturings (3 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 27 publications
6
20
2
Order By: Relevance
“…Callus development was not observed, which is positive for the clonal propagation of cultivars because the risk of genetic variability induction by somaclonal regeneration is reduced. This result is consistent with results obtained by Lin et al (1997;1998) and Nasri et al (2013) in alstroemeria, where callus production was not observed. Nevertheless, other studies suggested that shoots and leaves cultured in media supplemented with TDZ and IBA (Cruz et al, 2003) or BAP and KIN (Pedraza-Santos et al, 2006) tend to produce callus development with the potential to induce somatic embryogenesis.…”
Section: Direct Organogenesis From Aerial Explantssupporting
confidence: 93%
See 1 more Smart Citation
“…Callus development was not observed, which is positive for the clonal propagation of cultivars because the risk of genetic variability induction by somaclonal regeneration is reduced. This result is consistent with results obtained by Lin et al (1997;1998) and Nasri et al (2013) in alstroemeria, where callus production was not observed. Nevertheless, other studies suggested that shoots and leaves cultured in media supplemented with TDZ and IBA (Cruz et al, 2003) or BAP and KIN (Pedraza-Santos et al, 2006) tend to produce callus development with the potential to induce somatic embryogenesis.…”
Section: Direct Organogenesis From Aerial Explantssupporting
confidence: 93%
“…However, this method is not useful for clonal propagation of commercial varieties. More recently, studies have been conducted on micropropagation from aerial explants, such as floral apices (Pedraza-Santos et al, 2006), nodes with axil tissue (Kim et al, 2006) and leaf base (Nasri et al, 2013). Organs such as leaves and stems for use as explants show several advantages for in vitro propagation because they provide more material for propagation than rhizomes, and aerial explants potentially present less contamination than underground explants (Lin et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies related to in vitro propagation of alstroemeria have been performed using commercial varieties (Khaleghi et al, 2008;Pumisutapon et al, 2012;Hutchinson et al, 2014) and hybrids (Nasri et al, 2013), but little is known about micropropagation of the wild species of this genus.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro propagation has been also considered to propagate alstroemeria since this technique has several advantages, particularly in terms of efficiency (Yousef et al, 2007;Pumisutapon et al, 2011;Seyyedyousefi et al, 2013;Hutchinson et al, 2014). Rhizome sections have been the most common explant used for the in vitro propagation of alstroemeria (Pumisutapon et al, 2012;Shahriari et al, 2012), although some experiments have also considered aerial explants such as stem (Kim et al, 2006), leaf (Nasri et al, 2013) and flower buds (Pedraza-Santos et al, 2006). In addition to the type of explant, characteristics of the culture medium are crucial to achieving successful micropropagation.…”
Section: Introductionmentioning
confidence: 99%
“…After 15 days of acclimation of Alstroemeria ligtu, 80% of seedlings survived [61], whereas for the hybrid Alstroemeria pelegrina x A. pulchella this percentage was 87% after three months of acclimation [62]. In our case, the seedling survival of L. ovallei was almost 70% after three months of acclimation inside the growth chamber and 55% at the end of the acclimation process (greenhouse), which demonstrates that some Alstroemeriaceae species have a good response to the acclimation process.…”
Section: Seedling Survival and Rhizome Productionmentioning
confidence: 53%